2020
DOI: 10.26434/chemrxiv.13047863
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanosecond Photodynamics Simulations of a Cis-Trans Isomerization Are Enabled by Machine Learning

Abstract: <p>Photochemical reactions are being increasingly used to construct complex molecular architectures with mild and straightforward reaction conditions. Computational techniques are increasingly important to understand the reactivities and chemoselectivities of photochemical isomerization reactions because they offer molecular bonding information along the excited-state(s) of photodynamics. These photodynamics simulations are resource-intensive and are typically limited to 1–10 picoseconds and 1,000 trajec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…ML shows great promise in nonadiabatic excited-state simulations 16,17 as documented by recent works using NNs to construct excited-state energy landscapes to perform fewest-switches surface hopping MD at longer time scales or with more comprehensive ensemble averaging. 66,68,217 Similar progress has been achieved in nonadiabatic dynamics at metal surfaces, where NNs have been used to construct excited-state landscapes 4,218 and continuous representations of the electronic friction tensor 219 used in molecular dynamics with electronic friction simulations 220,221 . It is evident that ML methods will play an important role in extending the range of applications for MQCD methods in the coming years.…”
Section: ML Enables Classical and Quantum Dynamics For Systems Of Unp...mentioning
confidence: 92%
“…ML shows great promise in nonadiabatic excited-state simulations 16,17 as documented by recent works using NNs to construct excited-state energy landscapes to perform fewest-switches surface hopping MD at longer time scales or with more comprehensive ensemble averaging. 66,68,217 Similar progress has been achieved in nonadiabatic dynamics at metal surfaces, where NNs have been used to construct excited-state landscapes 4,218 and continuous representations of the electronic friction tensor 219 used in molecular dynamics with electronic friction simulations 220,221 . It is evident that ML methods will play an important role in extending the range of applications for MQCD methods in the coming years.…”
Section: ML Enables Classical and Quantum Dynamics For Systems Of Unp...mentioning
confidence: 92%
“…A similar idea has seen previous wide use for generating the initial conditions for FSSH simulations, though only the coordinate information is used in this study to generate the data set rather than both coordinate and velocity information as for generating the initial conditions for FSSH simulations. We also briefly mention that KRR has been recently used in combination with Wigner sampling for computing absorption cross sections, and a recent preprint has also used Wigner sampling in part to generate an initial data set for nonadiabatic machine learning-based dynamical simulation …”
Section: Theoretical Methodsmentioning
confidence: 99%
“…We also briefly mention that KRR has been recently used in combination with Wigner sampling for computing absorption cross sections, 37 and a recent preprint has also used Wigner sampling in part to generate an initial data set for nonadiabatic machine learning-based dynamical simulation. 38 However, if the true m and ω of the system are used for Wigner sampling, the resulting Gaussian is too broad to correctly sample the needed region of configurational space. Therefore, as outlined in the Supporting Information, the value of γ is fit to improve the prediction of the KRR model.…”
Section: ■ Theoretical Methodsmentioning
confidence: 99%
“…As another benefit of the ML models, it was shown that a large ensemble of trajectories could be calculated, still at a lower cost than a few trajectories with the reference method. 94 Recently, Li et al 669 The performance of KRR in comparison to NNs was assessed by us together with von Lilienfeld and co-workers. 95 The operator formalism 670 and the FCHL representation 127,530 were used to fit the three singlet states of CH 2 NH 2 + using the previously generated training set of 4000 data points.…”
Section: Of Secondary Outputsmentioning
confidence: 99%